Pengalaman Belajar Matematika Siswa melalui Pembelajaran Kooperatif Tipe Think Pair Share - Defi (Milenial: Journal for Teachers and Learning, 2024)
Mathematics is an essential subject in developing students’ logical, analytical, critical, and systematic thinking skills. However, in practice, many students perceive mathematics as difficult, which often leads to passive participation and a lack of confidence in expressing their ideas. One alternative solution is the implementation of the Think Pair Share (TPS) cooperative learning model, which provides opportunities for students to think individually, discuss with peers, and share their ideas with the class. This study aims to explore students’ learning experiences through the application of the TPS model in mathematics learning. The research employed a qualitative approach with a phenomenological design. The subjects were fifth-grade students at SDN 004 Sungai, selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using thematic analysis techniques. The findings reveal that in the think stage, students felt more prepared for discussion, although some still faced difficulties in solving problems independently. In the pair stage, students were more comfortable exchanging ideas with their partners, which improved conceptual understanding, although some remained passive. In the share stage, many students became more confident in presenting their answers to the class, while others were still reluctant due to fear of making mistakes. Supporting factors for TPS implementation included a conducive classroom atmosphere and clear teacher instructions, while inhibiting factors included limited time and unequal abilities between partners. This study concludes that TPS provides positive learning experiences, enhances participation, self-confidence, and conceptual understanding in mathematics learning, although it requires additional teacher strategies to optimize its effectiveness